The Lukumbi: a six-toned slit drum of the Batetela - Gilbert, Dorothy R. (International Library of African Music, 1955)
Three types of drums are used by the Batetela, a Bantu tribe situated between the Lomami and the Sankuru rivers in the Kasai Province of central Belgian Congo. The ngomo skin drum is used for dancing, usually accompanying the lukumbi, the six-toned slit drum. The ekuli, a small cylindrical two-toned drum, formerly used to signal victory in battle, is now used to call people to church and classes. The lukumbi is the most interesting and intricate of the three, and constitutes a highly developed poetic and musical art form as well as a means of communication.
Keywords: Ethnomusicology; Music; Drum; Tetela (African people); Performance; Slit drums; Musical instruments; Drum music; Belgian Congo; Drum (Instrument); Slit Drum (Instrument); Skin Drum (Instrument); Lukumbi (Instrument); Ngomo (Instrument); African Music